Impact of morphological furrows as lubricant reservoir on creation of oleophilic and oleophobic behaviour of metallic surfaces in scuffing. (December 2017) - Wojciechowski, L.; Kubiak, K.J.; Mathia, T.G.
Abstract: This paper analyses the key role of the surface morphology in the creation of oleophilic or oleophobic behaviour (via oil capacity) of metallic surfaces and its hypothetical influence on the initiation of the catastrophic mechanism of scuffing. Taking into consideration the fact that the commonly used roughness parameters do not correlate with the scuffing performance, the application of the morphological furrows to analysis of the susceptibility of metallic surfaces to this type of surface failure was proposed and elucidated. Furrows characteristic was based on the analysis of their three typical parameters (max. and mean depth and max. density, in the initial and scuffed surface state) in the mechanical and physicochemical aspects of the surface and lubricant relationship. Improved strategy offering the discriminating methodology of scuffing transition was presented and discussed. Obtained results enabled the identification furrows' parameters predisposed to scuffing prediction and therefore worthy to consideration for use in manufacturing of frictional operating metallic parts exposed to catastrophic failures. Highlights: The terms of oleophibility and oleophilicity were proposed and defined. Morphological furrows concept in the tribological surface characterization were presented. Furrows max. and mean depth and their max. density were applied to the surface description. The relationship between furrows parameters and scuffing activation was recognised. Furrows parameters best correlated with scuffing activation were determined.